Rhetoric of trans* identities: public reactions to private confessions - Abele, Kelsey T. (Kansas State University, 2016)
The year 2015 provided a hotbed of discussion about trans* identities. Caitlyn Jenner’s public announcement of her identity as transgender shortly followed by Rachel Dolezal unveiling as a woman with Caucasian heritage. Using publically accessible interviews such as the Diane Sawyer interview with Bruce Jenner, both of Matt Lauer’s conversations with Dolezal and Jenner, Melissa Harris-Perry’s interview with Dolezal, as well as two Vanity Fair stories provide a space for a closer examination of how trans* identities are negotiated in a conversational setting. Using Hecht’s (1993) communication theory of identity to investigate how the four proposed frames (personal, enactment, relationship, and communal) operate under the lens of trans* identities in flux. This thesis aims to explore the kinds of linguist framing motifs used by both an exemplar of the transgender community and an individual treading the barrier between Caucasian and black identities, ultimately leading to a discussion about how language confines personal and socially structure identity and identification. The implications of this identity work tangles with the reliance on personal experience as an expression of identity and its persuasive power to impact discourse. The linguistic tropes that confine identity expression inherently impact a community of individuals struggling to navigate trans* identity acceptance in a larger sphere.
Keywords: trans*; identity; identification; race; gender; language